Synthesis of New Furan Compounds: A Study towards Pyrrole Ring - Karaarslan, Muhsin; Demircan, Aydin (Asian Journal of Chemistry, 2010)
Synthesis towards the precursor 1 for radicalic reaction has been studied. 3-Methyl-5-(5-methylfuran-2-yl)-4,5-dihydro-isoxazole, (7) was obtained from vinyl furan. 2-(4-Iodo-pent-4-enyl)-4-methyl-6-(5-methyl-furan-2-yl)-[1,3]oxazinane (13) was generated using the amino alcohol 8 and corresponding aldehyde (11). Selective protection on the amino alcohol was achieved. Steric hindrance of amino group behaved obstructive to a condensation reaction.